Singularity and Statics Analysis of Redundant Parallel Mechanism - Tang Ke; Wan Xiaojin; Lu Kai (Jixie chuandong, 2019)
The singularity and statics performance of a 6-DOF mobile redundant parallel mechanism and its real-time optimization design are studied. The statics Jacobian matrix of this parallel mechanism is established,and the singularity and statics performance are analyzed. The statics transfer performance of parallel mechanism is improved by adjusting the leg position of the parallel mechanism. The performance spectrum based on the Jacobian matrix is drawn,the transfer performance of the statics force and moment of the parallel mechanism in different positions is observed intuitively. By above analysis shows that the redundant parallel mechanism can eliminate the singularity,while adjusting the leg position also greatly improves the static transfer performance of parallel mechanism.